Synthesis of acyclic nucleoside analogues based on 1,2,4-triazolo[1,5-a]pyrimidine-7-ones by one-step Vorbrüggen glycosylation - I. A. Khalymbadzha; S. L. Deev; T. S. Shestakova; V. L. Rusinov; O. N. Chupakhin (Chimica Techno Acta)
New analogues of acyclovir have been prepared by reacting 1,2,4-triazolo[1,5-a]pyrimidin-7-ones 1а-i and (2-acetoxyethoxy)methyl acetate 2 in the presence of trimethylsilyl trifluoromethanesulfonate as a catalyst. Thei nteraction between the compounds 1а-е and 2 has led to a mixture of N3 and N4 isomers. In contrast, the reaction of compounds 1g-i and 2 proceeded selectively to form N3 isomers. In the case of compounds 1a-c the predominant product is the one with the acyclic moiety in azine ring (N4 isomer). Interaction between 1d-f and 2 has led to mixtures comprising mainly N3 isomer. It has been found that the ratio of glycosylation products 1 and 2 are thermodynamically controlled. The structure of the obtained compounds has been proved by 1Н, 13С, two-dimensional 1Н-13С NMR spectroscopy and X-ray analysis.